Risk-neutral hedging of interest rate derivatives - Privault, Nicolas (2013)
In this paper we review the hedging of interest rate derivatives priced under the risk-neutral measure, and we compute self-financing hedging strategies for various derivatives using the Clark–Ocone formula.